(untitled) (Journal of Politics and International Studies, 2025)
In spite of being one of the most frequently used terms in the 21st Century, extremism is poorly understood and loosely defined. Seen either as a prerequisite to violence or a principal driver of terrorism, the term extremism has not only become derogative and pejorative but is also typically condemned and dismissed out of hand. It will be the contention of this paper that extremism, in and of itself, is not necessarily bad or wrong. Treating it otherwise is not only wrong-footed but also seriously risks undermining and sabotaging the prospects of all Prevention of Violent Extremism related policies and initiatives. It is therefore necessary to redress this gross policy neglect and academic oversight. To do so, we will first have to isolate extremism from violence and terrorism and then theorize and conceptualize it in its own right.